Lithium secondary battery having long life
By limiting the weight ratio of sulfur in the negative electrode of the lithium-sulfur battery and forming the SEI layer, the problems of negative electrode pollution and sulfur passivation during the charging and discharge process of the lithium-sulfur battery are solved, and high capacity retention and long life characteristics are achieved.
Patent Information
- Application Number
- CN202380053407.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-05-03
- Filing Date
- 2023-10-06
- Publication Date
- 2025-02-25
AI Technical Summary
Existing lithium-sulfur batteries are prone to negative electrode surface contamination and sulfur passivation during repeated charging and discharging, resulting in irreversible loss of active materials and shortening of life.
By limiting the proportion of sulfur weight to less than 3% of the total weight in the negative electrode of the lithium-sulfur battery, and forming a solid electrolyte interface (SEI) layer on the surface of the negative electrode, the passivation of sulfur and the contamination of the negative electrode are suppressed.
The high capacity retention rate and long life characteristics of lithium-sulfur batteries during repeated charging and discharging are realized, and they can maintain more than 80% of the initial capacity after more than 190 cycles, and have an energy density of more than 300 Wh/kg.
Smart Images

Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present disclosure relates to a lithium secondary battery, and more particularly, to a lithium-sulfur battery having a long lifespan.
[0002] This application claims priority to Korean Patent Application No. 10-2023-0058000 filed in Korea on May 3, 2023, and Korean Patent Application No. 10-2023-0133560 filed in Korea on October 6, 2023, the disclosures of which are incorporated herein by reference in their entirety. Background Art
[0003] As the application scope of lithium secondary batteries expands not only to mobile electronic devices but also to electric vehicles (EVs) and energy storage systems (ESSs), the demand for lithium secondary batteries having high capacity, high energy density, and long life is increasing.
[0004] Among various types of lithium secondary batteries, lithium-sulfur batteries are battery systems that use a sulfur-based material containing a sulfur-sulfur (SS) bond as a positive electrode active material, and use lithium metal, a carbon-based material capable of inserting / deinserting lithium ions, or silicon and tin capable of alloying with lithium as a negative electrode active material.
[0005] In lithium-sulfur batteries, sulfur is the main material of the positive electrode active material. It has low atomic mass, is very abundant in nature, can be found all over the world, is low cost, and is non-toxic and environmentally friendly.
[0006] In addition, lithium-sulfur batteries use the conversion reaction of lithium ions and sulfur (S8+16Li + +16e - → 8Li2S) has a theoretical specific capacity of 1675 mAh / g, and when lithium metal is used in the negative electrode, the theoretical energy density is 2600Wh / kg. This value is much higher than the theoretical energy density of other battery systems currently being studied (Ni-MH battery: 450 Wh / kg, Li-FeS battery: 480Wh / kg, Li-MnO2: 1000 Wh / kg, Na-S battery: 800 Wh / kg) and lithium-ion batteries (250 Wh / kg), so among the secondary batteries developed so far, lithium-sulfur batteries have attracted much attention for their high capacity, environmental protection and low cost.
[0007] During discharge, lithium-sulfur batteries undergo a reduction reaction in which sulfur accepts electrons at the positive electrode and, in this case, produces lithium (poly)sulfide (Li2S x, x = 1 to 8), and some lithium (poly) sulfides are easily dissolved in the electrolyte and completely reduced, and then precipitated on the negative electrode in the solid form of lithium sulfide (Li2S), or the lithium (poly) sulfides react with the lithium-containing metal of the negative electrode, which leads to surface contamination of the negative electrode, inducing sulfur (S) passivation on the negative electrode, resulting in irreversible loss of active materials, and this shuttling phenomenon hinders the long life characteristics.
[0008] Therefore, there is a need to develop a lithium-sulfur battery that can suppress passivation on the negative electrode caused by repeated charge and discharge and achieve long life characteristics. Summary of the invention
[0009] Technical issues
[0010] The present disclosure aims to solve the above-mentioned problems, and thus the present disclosure aims to provide a lithium-sulfur battery having a long life characteristic.
[0011] The present disclosure further aims to provide a lithium-sulfur battery with high energy density.
[0012] Technical Solution
[0013] In order to achieve the above objectives, according to one aspect of the present disclosure, a lithium-sulfur battery according to the following embodiments is provided.
[0014] According to a first embodiment, there is provided a lithium-sulfur battery comprising a positive electrode comprising a sulfur-carbon composite, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, wherein the negative electrode comprises a lithium metal layer and a solid electrolyte interface (SEI) layer on at least one surface of the lithium metal layer, and wherein the weight of sulfur (S) present in the negative electrode at a state of charge (SOC) of 100 is 3 wt % or less based on the total weight of the negative electrode.
[0015] According to the second embodiment, in the first embodiment, the lithium-sulfur battery may have a potential of 2.4 V to 2.7 V at SOC 100 .
[0016] According to a third embodiment, in the first or second embodiment, the weight of the sulfur (S) in the negative electrode may be 3 wt % or less based on the sum of the weights of the sulfur (S) and lithium (Li) in the negative electrode.
[0017] According to a fourth embodiment, in any one of the first to third embodiments, the weight of the sulfur (S) in the negative electrode may be 2 wt % or less based on the sum of weights of the sulfur (S) and the lithium (Li) in the negative electrode.
[0018] According to a fifth embodiment, in any one of the first to fourth embodiments, the weight of the sulfur (S) in the negative electrode may be 1 wt % or less based on the sum of weights of the sulfur (S) and the lithium (Li) in the negative electrode.
[0019] According to a sixth embodiment, in any one of the first to fifth embodiments, the negative electrode may have a thickness of 120 μm or less.
[0020] According to a seventh embodiment, in any one of the first to sixth embodiments, the negative electrode may have a thickness of 70 μm or less.
[0021] According to an eighth embodiment, in any one of the first to seventh embodiments, a sulfur / carbon weight ratio (S / C weight ratio) of the sulfur-carbon composite may be 2.5 g / g or less.
[0022] According to a ninth embodiment, in any one of the first to eighth embodiments, the positive electrode may include a current collector and a positive electrode active material layer including the sulfur-carbon composite, and the weight of the sulfur-carbon composite may be 90 wt % or more based on the total weight of the positive electrode active material layer.
[0023] According to a tenth embodiment, in any one of the first to ninth embodiments, a weight ratio of the electrolytic solution to sulfur in the sulfur-carbon composite (E1 / S weight ratio) may be 3.5 g / g or less.
[0024] According to an eleventh embodiment, in any one of the first to tenth embodiments, the electrolytic solution may include a nonaqueous solvent, a lithium salt, and an additive.
[0025] According to a twelfth embodiment, in any one of the first to eleventh embodiments, the additive may include a nitrogen compound.
[0026] According to a thirteenth embodiment, in any one of the first to twelfth embodiments, the additive may include lithium nitrate (LiNO 3 ).
[0027] According to a fourteenth embodiment, in any one of the first to thirteenth embodiments, the additive may include a nitrogen compound.
[0028] According to a fifteenth embodiment, in any one of the first to fourteenth embodiments, the additive may be contained in an amount of 1 wt % to 5 wt % based on the total weight of the electrolyte.
[0029] According to a sixteenth embodiment, in any one of the first to fifteenth embodiments, the lithium-sulfur battery may have a lifespan of 190 cycles or more when charge and discharge cycles are repeated at a rate of 0.3 to 0.5 C in a range of 1.8 V to 2.5 V at room temperature.
[0030] According to a seventeenth embodiment, in any one of the first to sixteenth embodiments, the room temperature may be a temperature of 23°C to 25°C.
[0031] According to an eighteenth embodiment, in any one of the first to seventeenth embodiments, the lithium-sulfur battery may have an energy density of 300 Wh / kg or more.
[0032] According to another aspect of the present disclosure, a method of evaluating the lifespan of a lithium-sulfur battery according to the following embodiment is provided.
[0033] According to a nineteenth embodiment, there is provided a method for evaluating the life of a lithium-sulfur battery, the lithium-sulfur battery comprising: a positive electrode comprising a sulfur-carbon composite, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, the negative electrode comprising a lithium metal layer and an SEI layer on at least one surface of the lithium metal layer, the evaluation method comprising:
[0034] When the weight of sulfur (S) present in the negative electrode at a state of charge (SOC) of 100 is 3 wt % or less based on the total weight of the negative electrode, the lithium-sulfur battery is determined to have a long lifespan.
[0035] According to the twentieth embodiment, in the nineteenth embodiment, when charge and discharge cycles are repeated at a rate of 0.3 to 0.5 C in the range of 1.8 V to 2.5 V at room temperature, the long-life lithium-sulfur battery may have a life of more than 190 cycles.
[0036] Beneficial Effects
[0037] According to one aspect, the lithium-sulfur battery of the present disclosure may exhibit excellent capacity retention upon repeated charge and discharge.
[0038] For example, the lithium-sulfur battery of the present disclosure can maintain more than 80% of the initial capacity after more than 190 charge and discharge cycles.
[0039] According to one aspect, the lithium-sulfur battery of the present disclosure may have a high energy density. In particular, the lithium-sulfur battery of the present disclosure may have an energy density of 300 Wh / kg or more.
[0040] According to one aspect, the lithium-sulfur battery of the present disclosure may have high energy density and long life characteristics. DETAILED DESCRIPTION
[0041] In the following, the present disclosure will be described in more detail.
[0042] It should be understood that when "comprising", "including" or "having" is used in the specification, the presence of the specified element is designated, and the presence or addition of one or more other elements is not excluded unless otherwise expressly specified.
[0043] Furthermore, the terms "about" and "substantially" as used herein are used in the sense of being equal to or close to when given the inherent manufacturing and material tolerances in the described circumstances, and are used to prevent unscrupulous infringers from unfairly taking advantage of the precise or absolute numbers stated for the purpose of facilitating understanding of the present disclosure.
[0044] Throughout the specification, "A and / or B" means A or B or both.
[0045] The term "composite" as used herein refers to a material formed by combining two or more materials and having physically and chemically distinct phases and more effective functions.
[0046] The term "(poly)sulfide" as used herein encompasses the concepts of "(poly)sulfide ions (S x 2- , 1≤x≤8)" and "lithium (poly)sulfide (Li2S x or Li2S x - 1≤x≤8)".
[0047] The term "polysulfide" as used herein encompasses the concepts of "polysulfide ions (S x 2- , 1<x≤8)" and "lithium polysulfide (Li2S x or Li2S x - 1<x≤8)".
[0048] Unless otherwise specified, the unit "mAh / g s " as used herein represents the capacity per weight of sulfur (S), and can be used interchangeably with other expressions such as mAh / g(s) or mAh / gs.
[0049] Unless otherwise specified, the unit "mg s / cm 2 " as used herein represents the weight of sulfur (S) per unit area, and can be used interchangeably with other expressions such as mg(s) / cm 2 or mAh / g as the loading amount.
[0050] The lithium-sulfur battery exhibits a battery capacity lower than the theoretical capacity because lithium (poly) sulfide generated by the reduction reaction of sulfur (S8) during charge and discharge dissolves out from the positive electrode into the electrolyte solution.
[0051] According to one aspect of the present disclosure, there is provided a lithium-sulfur battery having an excellent capacity retention rate after repeated charge and discharge.
[0052] The lithium-sulfur battery according to one aspect of the present disclosure includes: a positive electrode containing a sulfur-carbon composite, a negative electrode, and a separator interposed between the positive electrode and the negative electrode; and an electrolyte solution.
[0053] In one embodiment of the present disclosure, specifically, the lithium-sulfur battery includes an electrode assembly and a case accommodating the electrode assembly and the electrolyte solution, and the electrode assembly includes a positive electrode, a negative electrode, and a separator.
[0054] In this case, the negative electrode includes a lithium metal layer; and a solid electrolyte interface (SEI) layer on at least one surface of the lithium metal layer, and the weight of sulfur (S) present in the negative electrode at a state of charge (SOC) of 100% is 3% by weight or less based on the total weight of the negative electrode.
[0055] As described above, the lithium-sulfur battery includes inorganic sulfur (S8) as a positive electrode active material. In the lithium-sulfur battery, during discharge, lithium (poly) sulfide is generated at the positive electrode through a reduction reaction. When the generated lithium (poly) sulfide is dissolved by the electrolyte solution and dissolves out from the positive electrode into the electrolyte solution, the dissolved lithium (poly) sulfide reacts with the lithium metal of the negative electrode, resulting in the precipitation of lithium sulfide on the surface of the negative electrode, leading to the passivation of sulfur (S). It may cause damage to the negative electrode, resulting in a shortened lifespan of the lithium-sulfur battery.
[0056] Referring to this mechanism, the materials containing sulfur (S) obtained from the positive electrode active material of the lithium-sulfur battery are collectively referred to as "sulfur-based compounds". The sulfur-based compounds may include, for example, any sulfur-containing compounds that can be formed by the reduction reaction of inorganic sulfur (S8) or the oxidation reaction of lithium sulfide (Li2S). More specifically, they may include inorganic sulfur (S8), lithium sulfide (Li2S), lithium polysulfide (Li2S x , 1 < x ≤ 8), disulfide compounds, carbon-sulfur polymers ((C2S y )) n , y = 2.5 to 50, n ≥ 2) or mixtures thereof.
[0057] Specifically, the sulfur-based compounds may be inorganic sulfur (S8), lithium sulfide (Li2S), lithium polysulfide (Li2S x , 1 < x ≤ 8) or a mixture of two or more of them.
[0058] In the present disclosure, lithium (poly)sulfide can be represented by the chemical formula Li2S x (1≤x≤8), and in this case, lithium (poly)sulfide is used as a term including lithium sulfide (Li2S).
[0059] The inventors have surprisingly found that as the life of the lithium-sulfur battery becomes shorter during repeated charge and discharge, when the sulfur (S) content on the negative electrode is controlled to be lower than a predetermined level, the lithium-sulfur battery can have a capacity of more than 80% of the initial capacity at more than 190 charge and discharge cycles, or even more than 195 cycles, and the inventors have completed the present invention based on the finding.
[0060] According to one embodiment of the present disclosure, in order to prevent the degradation of the lithium-sulfur battery, the lithium-sulfur battery may include a nitrogen compound such as lithium nitrate (LiNO 3 ) as an additive to the electrolyte.
[0061] As described below, when the amount of the additive in the electrolyte is too high, the additive is not dissolved in the non-aqueous solvent, resulting in precipitation, which accelerates the degradation of the lithium-sulfur battery, so considering the solubility of the additive in the non-aqueous solvent, the content of the additive may be 5 wt % or less, for example, 1 wt % to 5 wt %, based on the total weight of the non-aqueous solvent, but the present disclosure is not limited thereto. The composition of the additive in the electrolyte will be described below.
[0062] According to one aspect of the present disclosure, a range of the sulfur (S) content in the negative electrode at SOC 100 (ie, when the lithium-sulfur battery is fully charged) is newly proposed.
[0063] Specifically, according to one aspect of the present disclosure, there is provided a lithium-sulfur battery, wherein the sulfur (S) content in the negative electrode at SOC 100 is 3 wt % or less based on the total weight of the negative electrode.
[0064] The negative electrode includes a lithium metal layer and an SEI layer on at least one surface of the lithium metal layer, and in order to achieve long life characteristics of the lithium-sulfur battery, the sulfur (S) content is limited to 3 wt % or less based on the sum of the weights of the lithium metal layer and the SEI layer.
[0065] In one embodiment of the present disclosure, the sulfur (S) content in the negative electrode may be, for example, 0 wt % to 3 wt %, 0.1 wt % to 3 wt %, 0.1 wt % to 3.0 wt %, 0.1 wt % to 2.5 wt %, 0.1 wt % to 2 wt %, 0.1 wt % to 1 wt % or 0.1 wt % to 0.5 wt %, based on the sum of the weights of the lithium metal layer and the SEI layer.
[0066] In one embodiment of the present disclosure, the lithium metal layer may include a lithium foil made of lithium metal as the negative electrode active material of the lithium-sulfur battery, or a lithium alloy foil made of a material capable of forming an alloy with lithium metal, and its thickness may be, for example, 140 μm or less.
[0067] In one embodiment of the present disclosure, the thickness of the lithium metal layer may be 140 μm or less, specifically 120 μm or less, 100 μm or less, more specifically 80 μm or less, or 70 μm or less. For example, the thickness of the lithium metal layer may be 20 μm to 140 μm, 20 μm to 120 μm, 20 μm to 100 μm, specifically 30 μm to 80 μm, 40 μm to 70 μm, 50 μm to 70 μm, 50 μm to 65 μm, 55 μm to 65 μm, or 55 μm to 60 μm. In one embodiment of the present disclosure, when the thickness of the lithium metal layer is within the above range, there may be advantages in terms of weight and energy density of the battery.
[0068] In the present disclosure, the thickness of the lithium metal layer can be measured by a known device for measuring the thickness of each component of the battery, for example, a thickness measuring machine of Mitutoyo can be used for measurement, but it is not limited thereto. In one embodiment of the present disclosure, the thickness of the negative electrode can be measured according to ASTM D374.
[0069] In one embodiment of the present disclosure, the SEI layer is a thin passivation layer formed on the surface of the lithium metal layer during charging during the activation process of the lithium-sulfur battery, and may protect lithium metal and inhibit electrolyte decomposition, but the present disclosure is not limited thereto.
[0070] In one embodiment of the present disclosure, the total thickness of the negative electrode including the lithium metal layer and the SEI layer may be 150 μm or less, specifically 120 μm or less, 100 μm or less, more specifically 70 μm or less. For example, the total thickness of the negative electrode may be in the range of 40 μm to 120 μm, such as 40 μm to 70 μm or 55 μm to 65 μm.
[0071] In one embodiment of the present disclosure, when the sulfur (S) content in the negative electrode is 3 wt % or less at SOC 100 (i.e., when the lithium-sulfur battery is fully charged), the lithium-sulfur battery can achieve long life characteristics. Specifically, the negative electrode can have a sulfur (S) content of 3 wt % or less based on the sum of the weights of sulfur (S) and lithium (Li) in the negative electrode. For example, the negative electrode can have a sulfur (S) content of 3 wt % or less, 2 wt % or less, 1 wt % or less, 0.5 wt % or less, or 0 wt % based on the sum of the weights of sulfur (S) and lithium (Li) in the negative electrode.
[0072] More specifically, the sulfur (S) content of the negative electrode may be in the range of 0 wt % to 3 wt %, 0.1 wt % to 3 wt %, 0.1 wt % to 2.5 wt %, 0.1 wt % to 2 wt %, 0.1 wt % to 1 wt %, or 0.1 wt % to 0.5 wt %, based on the sum of the weights of sulfur (S) and lithium (Li) in the negative electrode at SOC 100 (i.e., when the lithium-sulfur battery is fully charged).
[0073] In this case, 0 wt % not only means that sulfur (S) is not included, but also a trace amount of sulfur is measured as 0 wt % due to the limitation of quantifiable measurement or measurement error. Therefore, 0 wt % may actually be 0.1 wt % based on the total weight of the negative electrode.
[0074] In one embodiment of the present disclosure, the amount of the lithium (Li) in the negative electrode is 96 wt % or more, 99 wt % or more, 96 wt % to 100 wt %, 96 wt % to 99.9 wt %, or 99 wt % to 99.9 wt %, based on the sum of the weights of sulfur (S) and lithium (Li) in the negative electrode. When the lithium content is within the above range, the lithium-sulfur battery can achieve long life characteristics, based on the sum of the weights of sulfur (S) and lithium (Li) in the negative electrode at SOC 100 (i.e., when the lithium-sulfur battery is fully charged), but the present disclosure is not limited thereto.
[0075] In one embodiment of the present disclosure, the composition of the SEI layer may vary according to the composition of the lithium salt and additives used in the electrolyte of the lithium-sulfur battery, and is not limited to a specific composition.
[0076] In one embodiment of the present disclosure, the SEI layer may include, for example, Li—F functional groups.
[0077] In one embodiment of the present disclosure, in the lithium-sulfur battery at SOC 100, the elements contained in the negative electrode including the lithium metal layer and the SEI layer may include sulfur (S), lithium (Li), and fluorine (F). Specifically, the elements contained in the negative electrode may include sulfur (S), lithium (Li), and fluorine (F).
[0078] In one embodiment of the present disclosure, the sulfur (S) content of the lithium-sulfur battery may be 3 wt % or less, 2 wt % or less, 1 wt % or less, 0.5 wt % or less, 0.1 wt % or less, or 0 wt % based on the sum of the weights of sulfur (S), lithium (Li), and fluorine (F) in the negative electrode at SOC 100 (i.e., when the lithium-sulfur battery is fully charged). In this case, 0 wt % not only means that sulfur (S) is not included, but also trace amounts of sulfur are measured as 0 wt % due to limitations of quantifiable measurement or measurement errors.
[0079] In one embodiment of the present disclosure, the SEI layer may include, for example, a complex formed by a chemical reaction of the additive of the electrolyte with lithium metal as described below. In this case, the additive of the electrolyte may be, for example, a material containing nitrogen (N), and accordingly, the SEI layer may contain nitrogen (N).
[0080] Therefore, in one embodiment of the present disclosure, the sulfur (S) content of the lithium-sulfur battery may be 3 wt % or less, 2 wt % or less, 1 wt % or less, 0.5 wt % or less, 0.1 wt % or less, or 0 wt % based on the sum of the weights of sulfur (S), lithium (Li), and nitrogen (N) in the negative electrode at SOC 100 (i.e., when the lithium-sulfur battery is fully charged). In this case, as described above, 0 wt % not only means that sulfur (S) is not included, but also a trace amount of sulfur is measured as 0 wt % due to the limitation of quantifiable measurement or measurement error.
[0081] In another embodiment of the present disclosure, the sulfur (S) content of the lithium-sulfur battery may be 3 wt % or less, 2 wt % or less, 1 wt % or less, 0.5 wt % or less, 0.1 wt % or less, or 0 wt % based on the sum of the weights of sulfur (S), lithium (Li), fluorine (F), and nitrogen (N) in the negative electrode at SOC 100 (i.e., when the lithium-sulfur battery is fully charged).
[0082] Subsequently, a method of measuring the sulfur (S) content in the negative electrode will be described.
[0083] In one embodiment of the present disclosure, the SOC 100 may represent a fully charged state of a battery. For example, the SOC 100 may represent a charged state having a potential of 2.4 V to 2.7 V. Specifically, the SOC 100 may represent a charged state having a potential of 2.5 V.
[0084] Specifically, the sulfur (S) content in the negative electrode at SOC 100 can be measured by elemental analysis after disassembling the fully charged lithium-sulfur battery (eg, charged to reach 2.4 V to 2.7 V, specifically 2.5 V) and cleaning to remove the electrolyte from the negative electrode.
[0085] In one embodiment of the present disclosure, the elemental analysis can be performed, for example, using ion chromatography (IC) analysis, inductively coupled plasma optical emission spectrometer (ICP-OES) analysis, elemental analyzer (EA) analysis, ONH analysis, etc., but the elemental analysis method is not limited thereto. Therefore, the sulfur (S) content in the negative electrode based on the total weight of the negative electrode at SOC 100 or based on the sum of the weights of sulfur (S) and lithium (Li) in the negative electrode at SOC 100 can be measured by the above-mentioned elemental analysis, such as ICP-OES.
[0086] In one embodiment of the present disclosure, the lithium-sulfur battery may be activated prior to the measurement of the sulfur (S) content by discharging at a discharge rate of 0.5 C in the range of 1.8 V to 2.5 V and charging at a charge rate of 0.3 C at room temperature (wherein room temperature is 23° C. to 25° C.) for at least one cycle, for example, more than 5 cycles, or more than 10 cycles.
[0087] As described above, since the sulfur-based compound derived from the positive electrode causes sulfur (S) passivation on the negative electrode during discharge, the conventional lithium-sulfur battery deteriorates during repeated charge and discharge cycles, but according to one aspect of the present disclosure, by limiting the upper limit of the sulfur (S) content in the negative electrode at SOC 100 (i.e., when fully charged) to 3 wt % or less, specifically 2 wt % or less, 1 wt % or less, or 0.5 wt % or less, a lithium-sulfur battery with a long life can be provided.
[0088] Subsequently, each component of the lithium-sulfur battery other than the negative electrode will be described in detail.
[0089] positive electrode
[0090] In one embodiment of the present disclosure, the positive electrode may include a positive electrode current collector and a positive electrode active material layer coated on one or both surfaces of the positive electrode current collector.
[0091] The positive electrode current collector is not limited to a specific type and may include those current collectors that support the positive electrode active material and have high electrical conductivity without causing chemical changes to the battery. For example, the positive electrode current collector may include copper, stainless steel, aluminum, nickel, titanium, palladium, sintered carbon, or copper or stainless steel treated with carbon, nickel, or silver on the surface, as well as aluminum-cadmium alloy.
[0092] The positive electrode current collector may have fine irregularities on the surface to enhance the bonding strength with the positive electrode active material and may have various forms, such as a film, sheet, foil, mesh, net, porous body, foam, and non-woven fabric.
[0093] The positive electrode active material layer contains the positive electrode active material and may also contain a conductive material, a binder, and an additive.
[0094] In one embodiment of the present disclosure, the positive electrode active material contains a sulfur-carbon composite.
[0095] In one embodiment of the present disclosure, the sulfur-carbon composite may include a porous carbon material; and a chalcogenide compound, the chalcogenide compound being loaded onto at least one of the interior of the pores of the porous carbon material or the outer surface of the porous carbon material. Since sulfur itself, which is used as the positive electrode active material, does not have electrical conductivity, sulfur can be used in combination with a conductive material such as a carbon material, and the porous carbon material can be used to load sulfur. In addition, the chalcogenide compound may be added as the positive electrode active material and may include, for example, inorganic sulfur (S8), lithium sulfide (Li2S), lithium polysulfide (Li2S x , 1 < x ≤ 8), a disulfide compound, a carbon-sulfur polymer ((C2S y ), n , y = 2.5 to 50, n ≥ 2) or a mixture thereof. Preferably, the chalcogenide compound may be inorganic sulfur (S8).
[0096] In one embodiment of the present disclosure, the porous carbon material is not limited to a specific type and may include any type of porous carbon material that can load the chalcogenide compound as the positive electrode active material, provide a framework for uniformly and stably fixing the chalcogenide compound, and improve the electrical conductivity of the positive electrode.
[0097] Typically, the porous carbon material can be manufactured by carbonizing precursors of various carbon materials. The porous carbon material may include irregular pores. The average diameter of the pores may be in the range of 1 to 200 nm, and the porosity may be in the range of 10 to 90% by volume of the total volume of the porous carbon material. In the case where the average diameter of the pores is less than the above range, the pore size is at the molecular level, which makes sulfur penetration impossible, on the contrary, in the case where the average diameter of the pores exceeds the above range, the porous carbon material has low mechanical strength, which is not conducive to use in the electrode manufacturing process.
[0098] In one embodiment of the present disclosure, the "average diameter of the hole" can be measured by a known method for measuring the pore size of a porous material, and the measuring method is not limited to a specific method. For example, the pore size can be measured by scanning electron microscopy (SEM), field emission microscopy (FEM), laser diffraction or Brunauer-Emmett-Teller (BET) method. Measurement using laser diffraction can use, for example, a commercially available laser diffraction particle size measuring machine (e.g., Microtrac MT3000). In addition, the measurement performed by the BET method can, for example, use the BELSORP series analyzer of BEL Japan, but is not limited thereto.
[0099] In one embodiment of the present disclosure, "porosity" refers to the fraction of voids in a structure to the total volume, expressed as %, and can be used interchangeably with void fraction, porosity, etc. In the present disclosure, porosity measurement is not limited to a specific method, and according to one embodiment of the present disclosure, for example, porosity can be measured by a BET method using nitrogen or a Hg porosimeter and ASTM D2873.
[0100] The shape of the porous carbon material may be spherical, rod-like, needle-like, plate-like, tubular, or block-like, and may include but is not limited to any shape commonly used in the lithium-sulfur battery.
[0101] The porous carbon material may include any carbon material with a porous structure or a high specific surface area commonly used in the corresponding technical field. For example, the porous carbon material may include at least one selected from the group consisting of: graphite; graphene; carbon black, including Danka black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black; carbon nanotubes (CNT), including single-walled carbon nanotubes (SWCNT) and multi-walled carbon nanotubes (MWCNT); carbon fibers, including graphite nanofibers (GNF), carbon nanofibers (CNF) and activated carbon fibers (ACF); graphite, including natural graphite, artificial graphite, expandable graphite and activated carbon, but not limited thereto. Preferably, the porous carbon material may be a carbon nanotube.
[0102] In one embodiment of the present disclosure, the porous carbon material may include, for example, carbon nanotubes (CNTs).
[0103] In one embodiment of the present disclosure, the sulfur-carbon composite may have a sulfur / carbon weight ratio (S / C weight ratio) of 5 g / g or less, such as 4 g / g or less, more specifically 2.5 g / g or less, such as 2.3 g / g or less. For example, the sulfur-carbon composite may have an S / C weight ratio of 2.3 g / g. When the S / C ratio of the sulfur-carbon composite is within the above range, it may be desirable in terms of the ability (conductivity) of the sulfur-carbon composite to transport electrons and the electrochemical specific surface area, for example, the larger surface area of the sulfur-carbon composite may more effectively inhibit the dissolution of sulfur from the positive electrode, but the present disclosure is not limited thereto.
[0104] In one embodiment of the present disclosure, the S / C ratio may be calculated from the weight (g) of sulfur and the weight (g) of carbon present in the sulfur-carbon composite. Alternatively, the S / C ratio may be calculated from the weight (wt%) of sulfur and the weight (wt%) of carbon based on the total amount of the sulfur-carbon composite. The S / C ratio may be dimensionless.
[0105] In one embodiment of the present disclosure, the S / C weight ratio may have a value of, for example, 0.5 to 5.0, 0.5 to 4.0, 1.0 to 3.0, 1.5 to 2.5, 2.0 to 2.45, 2.25 to 2.35, or 2.3 to 3. For example, the S / C ratio may be calculated by the weight ratio of the inorganic sulfur (S8) / the weight of the porous carbon material. For example, the S / C ratio may be calculated by the weight ratio of S8 / CNT.
[0106] The method of manufacturing the sulfur-carbon composite is not limited to the specific method in the present disclosure, and may include methods commonly used in the corresponding technical field. For example, the sulfur-carbon composite can be manufactured by simply mixing sulfur with the porous carbon material and performing a heat treatment to produce a composite.
[0107] On the basis of the above composition, the positive electrode active material may further include at least one selected from transition metals, Group IIIA elements, Group IVA elements, sulfur compounds of these elements, or alloys of these elements and sulfur.
[0108] The transition metal may include Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Os, Ir, Pt, Au or Hg, the Group 13 element may include Al, Ga, In, Ti, and the Group 14 element may include Ge, Sn, Pb.
[0109] In one embodiment of the present disclosure, the content of the sulfur-carbon composite may be 50 wt % or more based on the total weight of the positive electrode. Specifically, based on the total weight of the positive electrode active material layer, the content of the sulfur-carbon composite may be, for example, 80 wt % or more, 90 wt % or more, or 95 wt % or more. Specifically, based on the total weight of the positive electrode active material layer, the content of the sulfur-carbon composite may be 80 wt % to 100 wt %, more specifically 85 wt % to 99 wt %, 90 wt % to 99 wt %, 95 wt % to 98 wt %, or 95 wt % to 97 wt %, or 96 wt %. In one embodiment of the present disclosure, the above amount of the sulfur-carbon composite may refer to the amount in the step of manufacturing the lithium-sulfur battery. In addition, in another embodiment of the present disclosure, the above amount of the sulfur-carbon composite may be measured by elemental analysis of the positive electrode after disassembling the lithium-sulfur battery charged at SOC100. When the amount of the sulfur-carbon composite is less than the above range, a larger amount of auxiliary materials such as a conductive material and a binder and a smaller amount of the sulfur-carbon composite make it difficult to realize a battery with high capacity and high energy density. On the contrary, when the amount of the sulfur-carbon composite is higher than the above range, the amount of the conductive material or the binder as described below is relatively insufficient, resulting in deterioration of physical properties of the electrode.
[0110] The conductive material may be a material that serves as a movement path for electrons from the current collector to the positive electrode active material by electrically connecting an electrolyte to the positive electrode active material, and may include, but is not limited to, any material having conductive properties as a constituent of an electrode that is physically different from the carbon contained in the sulfur-carbon composite.
[0111] In one embodiment of the present disclosure, the conductive material may include, for example: carbon black, such as Super-P, Danka black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, carbon black; carbon derivatives, such as carbon nanotubes or fullerenes; conductive fibers, such as carbon fibers or metal fibers; metal powders, such as fluorocarbons, aluminum, nickel powders; or conductive polymers, such as polyaniline, polythiophene, polyacetylene, polypyrrole (used alone or in combination).
[0112] In one embodiment of the present disclosure, based on the total weight of the positive electrode active material, the amount of the conductive material may be in the range of 0 to 40 wt%, 1 to 40 wt%, 15 to 40 wt%, 20 to 40 wt%, 25 to 35 wt%, 0 to 10 wt%, for example, 1 to 10 wt%. When the amount of the conductive material is less than the above range, the voltage and capacity are reduced due to poor electron transport between the positive electrode active material and the current collector. On the contrary, when the amount of the conductive material is greater than the above range, the proportion of the positive electrode active material is reduced, resulting in a reduction in the total energy (charge) of the battery, so it is desirable to determine the optimal amount within the above range.
[0113] In one embodiment of the present disclosure, the binder may be used to bond the positive electrode active material to the positive electrode current collector and connect the positive electrode active material in an organic manner to improve bonding strength, and may include any binder commonly used in the corresponding technical field.
[0114] For example, the adhesive may include one selected from the group consisting of: a fluororesin adhesive including polyvinylidene fluoride (PVdF), a polyvinylidene fluoride polymer containing at least one vinylidene fluoride repeating unit, polytetrafluoroethylene (PTFE) or a mixture thereof; a rubber adhesive including styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber, styrene-isoprene rubber; an acrylic adhesive; a cellulose adhesive including carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose; a polyol adhesive; a polyolefin adhesive including polyethylene, polypropylene; a polyimide adhesive; a polyester adhesive; a silane adhesive; a polyacrylic acid adhesive; and a polyacrylonitrile adhesive, or a mixture or copolymer thereof. In one embodiment of the present disclosure, the adhesive is a polyacrylate or salt (PAA).
[0115] In one embodiment of the present disclosure, the amount of the binder may be 1 to 10 wt % based on the total weight of the positive electrode active material layer. When the amount of the binder is less than the above range, the positive electrode active material and the conductive material may fall off due to reduced physical properties of the positive electrode, and when the amount of the binder is greater than the above range, in the positive electrode, a lower ratio of the positive electrode active material and the conductive material may reduce battery capacity, and it is desirable to determine the optimal amount within the above range.
[0116] In the present disclosure, a method of manufacturing a positive electrode for a lithium secondary battery is not limited to a specific method, and may include a method known to those skilled in the art or various modified methods.
[0117] For example, the positive electrode for a lithium secondary battery may be manufactured by preparing a positive electrode slurry composition having the above composition, and coating the composition on at least one surface of the positive electrode collector to form the positive electrode active material layer.
[0118] The positive electrode slurry composition includes the positive electrode active material described above, and may further include the binder, the conductive material, and a solvent.
[0119] The solvent includes any solvent that can uniformly disperse the positive electrode active material. The solvent may preferably be an aqueous solvent, most preferably water, and in this case, the water may be distilled water, deionized water. The solvent is not limited thereto, and if necessary, may include a lower alcohol that is easily mixed with water. The lower alcohol may include methanol, ethanol, propanol, isopropanol and butanol, and preferably, they may be used in combination with water.
[0120] The solvent may be included in an amount to ensure a sufficient viscosity level to facilitate coating, and the amount of the solvent may vary depending on the coating method and apparatus.
[0121] If necessary, the positive electrode slurry composition may further include materials commonly used in the corresponding technical field to improve functions. For example, the positive electrode slurry composition may further include a viscosity modifier, a flow aid, a filler, and the like.
[0122] The method for coating the positive electrode slurry composition is not limited to the specific method in the present disclosure, and may include, for example, a doctor blade, die casting, die coating, comma coating, screen printing. In addition, the positive electrode slurry may be coated on the positive electrode collector by forming on a substrate and pressing or laminating.
[0123] After the coating, a drying process may be performed to remove the solvent. The drying process may be performed at a sufficient level of temperature and time to remove the solvent, and the conditions may vary depending on the type of solvent, and the present disclosure is not limited to specific conditions. For example, the drying method may include drying by warm air, hot air and low humidity air, vacuum drying, and drying by (far) infrared radiation and electromagnetic radiation. The drying speed is adjusted to remove the solvent as quickly as possible within a speed range that prevents the positive active material layer from cracking or the positive active material layer from peeling off from the positive current collector due to stress concentration.
[0124] In addition, after the drying, the current collector may be pressed to increase the density of the positive electrode active material in the positive electrode. The pressing may include molding and rolling.
[0125] The positive electrode, specifically the positive electrode active material layer manufactured by the above composition and manufacturing method can have a porosity of 50 to 80 volume %, specifically 60 to 75 volume %. When the porosity of the positive electrode is less than 50 volume %, due to the high filling degree of the positive electrode slurry composition comprising the positive electrode active material, the conductive material and the binder, it is impossible to maintain a sufficient amount of electrolyte for ion conductivity and / or conductivity in the positive electrode active material, resulting in the output characteristics or cycle characteristics of the battery being deteriorated, and the problem of reduced overvoltage and discharge capacity of the battery becoming worse. On the contrary, when the porosity of the positive electrode is higher than 80 volume %, the excessively high porosity reduces the physical connection and electrical connection with the collector, resulting in low adhesion strength and poor reaction, and the high electrolyte filling degree reduces the energy density of the battery, so the porosity of the positive electrode is appropriately adjusted within the above range.
[0126] In one embodiment of the present disclosure, the sulfur loading in the positive electrode may be 2.5 mg(s) / cm 2 Below, for example 0 to 2.5 mg(s) / cm 2 , from 0.1 to 2.4 mg(s) / cm 2 or 1.7 to 2.1 mg(s) / cm 2 . The sulfur loading amount may be a value calculated from the total weight of sulfur (S) contained in the positive electrode as the positive electrode active material. In this case, the weight of sulfur in the positive electrode may be measured from the positive electrode active material used in the manufacturing step, or may be measured by performing thermogravimetric analysis (TGA) on the positive electrode after manufacturing. In another embodiment, a fully charged lithium-sulfur battery is disassembled under an inert atmosphere to obtain a positive electrode, and then the positive electrode is washed with an appropriate washing solvent and dried, and then the positive electrode active material layer is scraped off. The content of sulfur (S) derived from the active material may be measured and calculated by performing thermogravimetric analysis (TGA) on the obtained result, but the measuring method is not limited thereto.
[0127] In another embodiment of the present disclosure, the sulfur loading in the positive electrode can be 3 mAh / cm 2 Below, specifically 0 to 3 mAh / cm 2 For example, the sulfur loading in the positive electrode may be 0.1 to 2.9 mAh / cm 2 , 0.5 to 2.8 mAh / cm 2 , 1 to 2.7 mAh / cm 2 , 1.5 to 2.6 mAh / cm 2 , or 2.0 to 2.5 mAh / cm 2The loading amount of sulfur may be a capacity value of an electrode calculated from the total weight of sulfur (S) measured as the positive electrode active material contained in the positive electrode.
[0128] negative electrode
[0129] The negative electrode may include a negative electrode current collector and a negative electrode active material layer formed on at least one surface of the negative electrode current collector. Alternatively, the negative electrode may be an independent lithium metal plate or lithium metal foil without a current collector.
[0130] In one embodiment of the present disclosure, the negative electrode current collector supports a negative electrode active material, and may include those described in the positive electrode current collector.
[0131] The negative electrode active material may include a material capable of reversibly inserting or deinserting lithium (Li + ) materials, materials that can reversibly form lithium-containing compounds by reacting with lithium ions, and lithium metal or lithium alloys.
[0132] The reversible insertion and extraction of lithium ions (Li + ) can be, for example, crystalline carbon, amorphous carbon or a mixture thereof. + The material that reversibly forms a lithium-containing compound by reacting with tantalum (tantalum) may be, for example, tin oxide, titanium nitrate or silicon. The lithium alloy may be, for example, an alloy of lithium (Li) and at least one metal selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al) and tin (Sn).
[0133] Diaphragm
[0134] The separator separates or insulates the positive electrode from the negative electrode and enables lithium ions to be transferred between the positive electrode and the negative electrode, and may be made of a porous non-conductive or insulating material, and includes any separator commonly used in lithium secondary batteries without limitation. The separator may be an independent member such as a film, and may be a coating added to the positive electrode and / or the negative electrode.
[0135] Preferably, the separator may have low electrolyte ion transport resistance and high electrolyte wettability.
[0136] In one embodiment of the present disclosure, the separator may include a porous substrate, and the porous substrate may include any type of porous substrate commonly used in secondary batteries. The separator may include a porous polymer film used alone or in a stack, for example, a non-woven fabric made of high melting point glass fiber, polyethylene terephthalate fiber or a polyolefin-based porous film, but is not limited thereto.
[0137] In the present disclosure, the porous substrate is not limited to a specific material and may include any of the porous substrates generally used in electrochemical devices. For example, the porous substrate may include at least one material selected from the group consisting of polyolefins (such as polyethylene, polypropylene), polyesters (such as polyethylene terephthalate, polybutylene terephthalate), polyamides, polyacetals, polycarbonates, polyimides, polyetheretherketones, polyethersulfones, polyphenylene oxides, polyphenylene sulfides, polyethylene naphthalate, polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl chloride, polyacrylonitrile, cellulose, nylon, poly(p-phenylene benzodione), ... azoles) and polyarylates.
[0138] In one embodiment of the present disclosure, the thickness of the porous substrate is not limited to a specific range, but may be 1 to 100 μm, preferably 5 to 50 μm. The thickness range of the porous substrate is not limited to the above range, but when the thickness is too small and below the above lower limit, poor mechanical properties may cause the separator to be damaged during use of the battery.
[0139] In one embodiment of the present disclosure, the average diameter and porosity of pores present in the porous substrate are also not limited to specific ranges, but may be 0.001 to 50 μm and 10 to 95 volume %, respectively.
[0140] In one embodiment of the present disclosure, the separator may further include a porous coating layer on at least one surface of the porous substrate, the porous coating layer including inorganic particles and a binder.
[0141] In one embodiment of the present disclosure, the inorganic particles and the binder contained in the porous coating layer are not limited to specific types and may include those commonly used in the porous coating layer of the separator, and a manufacturing method thereof is not limited to a specific method.
[0142] Electrolyte
[0143] The electrolyte solution includes a non-aqueous solvent as a medium for the movement of ions involved in the electrochemical reaction of the lithium-sulfur battery and a lithium salt as an electrolyte.
[0144] The electrolyte may include, but is not limited to, any composition used in the lithium secondary battery, specifically the lithium-sulfur battery.
[0145] In one embodiment of the present disclosure, the electrolyte may include the nonaqueous solvent, the lithium salt, and an additive.
[0146] In one embodiment of the present disclosure, the nonaqueous solvent is not limited to a specific type and may include any type of solvent used in the lithium-sulfur battery, and may include, for example, ether solvents, esters, amides, linear carbonates, and cyclic carbonates.
[0147] In one embodiment of the present disclosure, the ester may include, for example, any one selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone and ε-caprolactone or a mixture thereof, but is not limited thereto.
[0148] In one embodiment of the present disclosure, the linear carbonate may generally include, for example, any one selected from the group consisting of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate and ethyl propyl carbonate or a mixture thereof, but is not limited thereto.
[0149] In one embodiment of the present disclosure, the cyclic carbonate may include, for example, any one selected from the group consisting of ethylene carbonate, propylene carbonate, 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, vinylene carbonate, vinyl ethylene carbonate, and halides thereof. The halides may include, for example, fluoroethylene carbonate, but are not limited thereto.
[0150] In one embodiment of the present disclosure, the non-aqueous solvent may include an ether-based solvent.
[0151] In one embodiment of the present disclosure, based on the total volume of the non-aqueous solvent, the content of the ether solvent may be 60% by volume or more, for example, 60% by volume to 100% by volume, 70% by volume to 100% by volume, 80% by volume to 100% by volume, 85% by volume to 100% by volume, 90% by volume to 100% by volume, 95% by volume to 100% by volume, 98% by volume to 100% by volume, 90% by volume to 98% by volume, or 90% by volume to 95% by volume. When the amount of the ether solvent is within the above range based on the total volume of the non-aqueous solvent, the solubility of components of the electrolyte such as lithium salts may be increased, but the present disclosure is not limited thereto.
[0152] In one embodiment of the present disclosure, the ether solvent may include acyclic ether, cyclic ether or a mixture thereof. As for the non-aqueous solvent, an ether solvent may be preferably used in terms of the solubility of the lithium salt and / or additives described below.
[0153] In one embodiment of the present disclosure, the acyclic ether may include, for example, at least one selected from the group consisting of dimethyl ether, diethyl ether, dipropyl ether, dibutyl ether, diisobutyl ether, ethyl methyl ether, ethyl propyl ether, ethyl tert-butyl ether, dimethoxymethane, trimethoxymethane, dimethoxyethane, diethoxyethane, dimethoxypropane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, ethylene glycol divinyl ether, diethylene glycol divinyl ether, triethylene glycol divinyl ether, dipropylene glycol dimethyl ether, butylene glycol ether, diethylene glycol ethyl methyl ether, diethylene glycol isopropyl methyl ether, diethylene glycol butyl methyl ether, diethylene glycol tert-butyl ethyl ether and ethylene glycol ethyl methyl ether. Preferably, the non-cyclic ether may include at least one selected from the group consisting of dimethyl ether, dimethoxyethane, diethoxyethane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether, and more preferably dimethoxyethane.
[0154] In one embodiment of the present disclosure, the cyclic ether may include, for example, at least one selected from the group consisting of 2-methylfuran, 1,3-dioxolane, 4,5-dimethyldioxolane, 4,5-diethyl-dioxolane, 4-methyl-1,3-dioxolane, 4-ethyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, 2,5-dimethoxytetrahydrofuran, Preferably, the cyclic ether may include at least one selected from the group consisting of 2-methylfuran, 1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran and 2,5-dimethyltetrahydrofuran, more preferably 2-methylfuran.
[0155] In one embodiment of the present disclosure, the non-aqueous solvent may include a mixture of acyclic ethers and cyclic ethers.
[0156] In one embodiment of the present disclosure, the non-aqueous solvent may include dimethoxyethane (DME) and 2-methylfuran (2-MeF).
[0157] In one embodiment of the present disclosure, the volume ratio (volume / volume) of the non-cyclic ether and the cyclic ether may be 5:95 to 95:5 (volume / volume), specifically 95:5 to 50:50, more specifically 90:10 to 70:30, 85:15 to 75:25, or 80:20. In the present disclosure, the volume ratio corresponds to the ratio of "volume % of non-cyclic ether": "volume % of cyclic ether" in the ether-based solvent.
[0158] In one embodiment of the present disclosure, in terms of the solubility of the electrolyte, the non-aqueous solvent may not include the carbonate-based solvent. Alternatively, the non-aqueous solvent may include a very small amount of the carbonate-based solvent so that the carbonate-based solvent does not affect the solubility of the lithium salt, for example, when the non-aqueous solvent includes the carbonate-based solvent, based on the gross weight of the lithium secondary battery electrolyte, the amount of the carbonate-based solvent may be less than 3 wt%, less than 2 wt%, less than 1 wt%, less than 0.5 wt% or 0 wt% (i.e., none).
[0159] In one embodiment of the present disclosure, the lithium salt is not limited to a specific type and may include those lithium salts used as electrolytes for lithium secondary batteries. The lithium salt may include, for example, LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiC4BO8, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, (CF3SO2)2NLi, (C2F5SO2)2NLi, (SO2F)2NLi, (CF3SO2)3CLi, lithium chloroborane, lithium lower aliphatic carboxylate, lithium tetraphenylborate, lithium imide or a mixture thereof.
[0160] In one embodiment of the present disclosure, the concentration of the lithium salt may be appropriately determined from the perspective of ion conductivity and solubility, and may be, for example, 0.1 to 4 M, preferably 0.25 to 2 M, 0.5 to 2 M, or 0.5 to 1.5 M. When the concentration of the lithium salt is within the above range, ion conductivity suitable for battery operation or a suitable viscosity of the electrolyte may be ensured, thereby improving the mobility of lithium ions and suppressing the decomposition reaction of the lithium salt itself, but the present disclosure is not limited thereto.
[0161] In one embodiment of the present disclosure, the electrolyte may further include additives, such as nitrogen compounds, on the basis of the lithium salt, to improve the conductivity of the electrolyte and increase the life of the lithium-sulfur battery.
[0162] Specifically, the effect of the nitrogen compound is not limited thereto, but for example, the nitrogen compound may inhibit the reduction reaction of polysulfides generated during charge and discharge of the lithium-sulfur battery, thereby preventing irreversible consumption of polysulfides, whereby the performance of the lithium-sulfur battery is improved.
[0163] In one embodiment of the present disclosure, the additive such as a nitrogen compound is not limited to a specific type, and may include those nitrogen compounds that stably form the SEI layer of the negative electrode and improve the charge and discharge efficiency, and may include, for example, a nitric acid compound, a nitrous acid compound, or a mixture thereof.
[0164] In one embodiment of the present disclosure, the nitrogen compound can be, for example, selected from the group consisting of: inorganic nitric acid or nitrous acid compounds, such as lithium nitrate (LiNO3), potassium nitrate (KNO3), cesium nitrate (CsNO3), barium nitrate (Ba(NO3)2), ammonium nitrate (NH4NO3), lithium nitrite (LiNO2), potassium nitrite (KNO2), cesium nitrite (CsNO2), ammonium nitrite (NH4NO2); organic nitric acid or nitrous acid compounds, such as methyl nitrate, dialkyl imidazolium nitrate, guanidine nitrate, imidazolium nitrate, pyridinium nitrate, ethyl nitrite, propyl nitrite, butyl nitrite, amyl nitrite, octyl nitrite; organic nitro compounds, such as nitromethane, nitropropane, nitrobutane, nitrobenzene, dinitrobenzene, nitropyridine, dinitropyridine, nitrotoluene, dinitrotoluene and combinations thereof, and preferably can include lithium nitrate.
[0165] In one embodiment of the present disclosure, the electrolyte may include a non-aqueous solvent and two types of lithium salts. In this case, the two types of lithium salts are different from each other, and one type of lithium salt may be a nitrogen-containing lithium salt, and the other type of lithium salt may be a nitrogen compound, such as lithium nitrate (LiNO3). For example, the two types of lithium salts may include LiTFSI as the electrolyte and LiNO3 as the additive.
[0166] In one embodiment of the present disclosure, the content of the nitrogen compound may be, for example, 1 wt % to 10 wt %, 1 wt % to 8 wt %, 1 wt % to 6 wt %, 1 wt % to 5 wt %, 1.0 wt % to 5.0 wt %, 2.0 wt % to 5.0 wt %, 2.0 wt % to 4.9 wt %, 2.1 wt % to 3.5 wt %, or 3 wt % to 5 wt %, based on the total weight of the electrolyte, but is not limited thereto. When the nitrogen compound is included in the above amount, the nitrogen compound may improve the conductivity of the electrolyte and may inhibit the reduction reaction of polysulfides when used in the lithium-sulfur battery, but the present disclosure is not limited thereto.
[0167] In one embodiment of the present disclosure, the concentration of the nitrogen compound in the electrolyte is in the range of 0.15 to 1.5 M (mol / L), specifically 0.20 to 1.0 M, 0.25 to 0.80 M, or 0.30 to 0.60 M. When the concentration of the nitrogen compound is within the above range, the nitrogen compound can improve the conductivity of the electrolyte and suppress the increase in the amount of sulfur in the negative electrode caused by the reduction reaction of (poly)sulfides when used in the lithium-sulfur battery, thereby preventing the degradation of the battery.
[0168] In another embodiment of the present disclosure, the ratio of the molar concentration of the lithium salt to the molar concentration of the additive (e.g., the nitrogen compound) may be, for example, 0.5 to 6.0 (molar concentration of the lithium salt / molar concentration of the additive), 0.5 to 5.5 (molar concentration of the lithium salt / molar concentration of the additive), 0.5 to 5.0, 0.90 to 5.0, 1.0 to 4.0, 1.0 to 3.0, or 1.5 to 2.5. When the ratio of the molar concentration of the lithium salt to the molar concentration of the additive is within the above range, the appropriate ion conductivity and viscosity of the electrolyte may be ensured, thereby improving the mobility of lithium ions and suppressing the decomposition reaction of the lithium salt itself, but the present disclosure is not limited thereto.
[0169] In another embodiment of the present disclosure, the sum of the concentrations of the lithium salt and the additive in the electrolyte (i.e., the total concentration) may be, for example, 0.5 M or more, specifically 0.9 M or more, for example, 0.9 M to 2 M, 0.9 M to 1.5 M, or 1.0 M to 1.5 M. When the sum of the concentrations of the lithium salt and the additive in the electrolyte is within the above range, the ion conductivity and viscosity of the electrolyte may be ensured, thereby improving the mobility of lithium ions and suppressing the decomposition reaction of the lithium salt itself, but the present disclosure is not limited thereto.
[0170] In one embodiment of the present disclosure, the lithium-sulfur battery may have a varying energy density depending on the ratio of the electrolyte to the positive electrode active material. The smaller the ratio of the electrolyte to the positive electrode active material, the greater the energy density of the lithium-sulfur battery, for example, the weight ratio of the electrolyte to the sulfur in the sulfur-carbon composite (E1 / S weight ratio) may be 3.5 g / g or less.
[0171] In one embodiment of the present disclosure, the lithium-sulfur battery may be manufactured, for example, with an El / S ratio of 3.0 g / g or less, or 2.9 g / g or less.
[0172] According to one embodiment of the present disclosure, long life characteristics may be achieved by limiting the sulfur (S) content in the negative electrode to less than 3 wt %, specifically 3.0 wt % or less, particularly 2.0 wt % or less at SOC 100 as described above.
[0173] In the present disclosure, the long life characteristic of the lithium-sulfur battery indicates a high capacity retention rate after repeated charge and discharge cycles.
[0174] In one embodiment of the present disclosure, the lithium-sulfur battery can maintain more than 80% of the initial capacity after 190 repeated charge and discharge cycles. Specifically, after at least 190 repeated charge and discharge cycles at a rate of 0.3 to 0.5 C in the range of 1.8 V to 2.5 V at room temperature, the lithium-sulfur battery can have more than 80% of the capacity measured in the first charge and discharge cycle.
[0175] In one embodiment of the present disclosure, the room temperature may be, for example, 23°C to 25°C, specifically 23°C.
[0176] In one embodiment of the present disclosure, the charge and discharge rate may be a 0.3 C rate or a 0.5 C rate, and may be, for example, a charge rate of 0.3 C and a discharge rate of 0.5 C, but the charge and discharge rate is not limited to a specific rate and may include any charge and discharge rate within the above rate range.
[0177] In one embodiment of the present disclosure, the energy density of the lithium-sulfur battery may be, for example, 300 Wh / kg or more.
[0178] In one embodiment of the present disclosure, the energy density of the lithium-sulfur battery can be measured by a known method, and the measuring method is not limited to a specific method. For example, the energy density of the lithium-sulfur battery can be measured, for example, by discharging at a rate of 0.5 C in the range of 1.8 V to 2.5 V and charging at a rate of 0.3 C at a room temperature of 23°C.
[0179] In one embodiment of the present disclosure, the lithium-sulfur battery may have various shapes, such as a coin, a pouch, or a cylinder, but is not limited thereto.
[0180] According to another aspect of the present disclosure, a method of evaluating the lifespan of a lithium-sulfur battery is provided.
[0181] In one embodiment of the present disclosure, the lithium-sulfur battery to be subjected to life evaluation contains a positive electrode including a sulfur-carbon composite, a negative electrode, a separator between the positive electrode and the negative electrode, and an electrolyte.
[0182] Specifically, the lithium-sulfur battery may include an electrode assembly including the positive electrode, the negative electrode, and the separator, and the electrode assembly is accommodated in a case together with the electrolyte.
[0183] In this case, the negative electrode includes the lithium metal layer and the SEI layer on at least one surface of the lithium metal layer.
[0184] The evaluation method includes determining that the lithium-sulfur battery has a long life when the sulfur (S) content is 3 wt % or less based on the total weight of the negative electrode at SOC 100.
[0185] In one embodiment of the present disclosure, the long-life lithium-sulfur battery may be, for example, a battery having a life of 190 cycles or more, particularly 200 cycles or more, after repeated charge and discharge cycles at a rate of 0.3 to 0.5 C in the range of 1.8 V to 2.5 V at room temperature.
[0186] In one embodiment of the present disclosure, the lithium-sulfur battery to be evaluated for life is preferably a battery activated by, for example, initial discharge and repeated charge and discharge. For example, the lithium-sulfur battery to be evaluated for life may preferably be a battery activated by repeated charge and discharge for 1 to 20 cycles, 5 to 15 cycles, or at least 10 cycles (e.g., 10 cycles), but the present disclosure is not limited thereto.
[0187] In one embodiment of the present disclosure, the lithium-sulfur battery to be subjected to lifetime evaluation may be activated by 0.5 C discharge and 0.3 C charge.
[0188] In one embodiment of the present disclosure, the charge and discharge of the lithium-sulfur battery to be evaluated for life span may be performed within a range of 1.8 V to 2.5 V.
[0189] Furthermore, activation of the lithium-sulfur battery to be subjected to life evaluation may be performed at room temperature, and may be performed at, for example, 23°C to 25°C, for example, 23°C.
[0190] In one embodiment of the present disclosure, the lithium-sulfur battery may be discharged at 0.5 C and charged at 0.3 C in the range of 1.8 V to 2.5 V at a room temperature of 23° C. to 25° C.
[0191] Hereinafter, embodiments will be described to help understand the present disclosure, but the following embodiments are provided by way of example, and it will be apparent to those skilled in the art that various changes and modifications may be made thereto within the technical aspects and scope of the present disclosure, and such changes and modifications fall within the scope of the appended claims.
[0192] [Manufacturing of lithium-sulfur batteries]
[0193] Example 1
[0194] Inorganic sulfur (S8) and carbon nanotubes (CNT) as positive electrode active materials were mixed to prepare a sulfur-carbon composite (S / C weight ratio = 2.3), and 96 wt % of the prepared sulfur-carbon composite and 4 wt % of polyacrylate or salt (PAA) as a binder were mixed to prepare a positive electrode slurry composition. The positive electrode slurry composition was coated on an aluminum current collector and dried to manufacture a positive electrode. The loading amount of the manufactured positive electrode was 2.08 mg(s) / cm 2 (2.5 mAh / cm 2 ).
[0195] For the negative electrode, 60 μm thick lithium metal was used.
[0196] The positive electrode and the negative electrode were placed opposite to each other with a polyethylene separator having a thickness of 16 μm and a porosity of 46 volume % interposed therebetween to prepare an electrode assembly.
[0197] The prepared electrode assembly was housed in a pouch case, and an electrolyte containing 0.75 M lithium salt (LiTFSI) and 2.1 wt % lithium nitrate (LiNO3) dissolved in a mixed solvent of dimethoxyethane (DME): 2-methylfuran (2-MeF) in a volume ratio of 8:2 was injected at an El / S ratio of 2.9 g / g to manufacture a lithium-sulfur battery. Therefore, the concentration of the nitrogen compound LiNO3 in the electrolyte was 0.33 M.
[0198] Example 2
[0199] A lithium-sulfur battery was manufactured by the same method as in Example 1, except that 3.5 wt % of lithium nitrate (LiNO 3 ) was dissolved in the electrolyte.
[0200] Example 3
[0201] A lithium-sulfur battery was manufactured by the same method as in Example 1, except that 5.0 wt % of lithium nitrate (LiNO 3 ) was dissolved in the electrolyte.
[0202] Comparative Example 1
[0203] A lithium-sulfur battery was manufactured by the same method as in Example 1, except that 0.8 wt % of lithium nitrate (LiNO 3 ) was dissolved in the electrolyte.
[0204] Comparative Example 2
[0205] A lithium-sulfur battery was manufactured by the same method as in Example 1, except that 0.4 wt % of lithium nitrate (LiNO 3 ) was dissolved in the electrolyte.
[0206]
[0207] [Evaluation of energy density of lithium-sulfur batteries]
[0208] The energy density of the lithium-sulfur battery was measured while discharging to 1.8 V at a 0.5 C rate and charging to 2.5 V once at the same rate and then discharging to 1.8 V once at a 0.5 C rate at room temperature (23° C.).
[0209] It was confirmed that the energy density of the lithium-sulfur batteries according to the examples and comparative examples satisfied 320 Wh / kg.
[0210] [Evaluation of Sulfur (S) Content in the Negative Electrode at SOC 100]
[0211] Each of the lithium-sulfur batteries of Examples 1 to 3 and Comparative Examples 1 and 2 manufactured as described above was activated by charging and discharging for 10 cycles at a 0.5 C discharge rate and a 0.3 C charge rate in the range of 1.8 V to 2.5 V at room temperature (23° C.), and was disassembled at SOC 100 to obtain the negative electrode.
[0212] In this case, the obtained negative electrode includes the lithium metal layer used to manufacture the lithium-sulfur battery and the SEI layer formed by discharge and recharge.
[0213] In order to obtain the negative electrode, the lithium-sulfur battery to be measured is disassembled to separate the positive electrode / separator / negative electrode, and the separated negative electrode is placed in a container containing a set mass of solvent and washed for more than 5 minutes. In this case, the same solvent as the non-aqueous solvent in the electrolyte is used.
[0214] Analysis was performed to determine the amounts of lithium (Li), sulfur (S), nitrogen (N), and fluorine (F) in the obtained negative electrode, and the analysis results are shown in Table 2 below.
[0215] The analytical method for determining the amounts of lithium (Li), sulfur (S), nitrogen (N), and fluorine (F) was performed as follows.
[0216] First, to analyze lithium, sulfur, and fluorine, the weight of a predetermined amount of sample is measured in a moisture-controlled drying chamber, and a primary oxidation reaction is induced using water. After the primary oxidation reaction, nitric acid is added to dissociate the substances in the sample in an ionic state. The treated solution is quantitatively analyzed using ICP-OES (or ICP-MS). To determine the fluorine content, the solution subjected to primary oxidation is immediately quantitatively analyzed using IC.
[0217] To determine the nitrogen content, a predetermined amount was wrapped with paraffin film in a drying chamber, the wrapped sample was pyrolyzed in an oxygen-filled atmosphere using an oxygen combustion chamber (explosion device), and the vaporized nitrogen was dissolved in the internal solvent to saturation. The solution that absorbed nitrogen was quantitatively analyzed using IC.
[0218] The mass of each element analyzed by the above method was calculated as weight percentage based on the total weight of the negative electrode, and is shown in the following Table 2. The sum of the mass of each element analyzed is the total weight of the negative electrode.
[0219] [Lifespan evaluation]
[0220] Each of the lithium-sulfur batteries of Examples 1 to 3 and Comparative Examples 1 and 2 manufactured as described above was activated by discharging at a 0.5 C rate and charging at a 0.3 C rate in the range of 1.8 V to 2.5 V at room temperature (23° C.), and the charge and discharge process was repeated at a 0.5 C rate. At the time point when the lithium-sulfur battery maintained 80% of the capacity based on the battery capacity measured in the first cycle after activation, the number of cycles until then was measured, and the results are shown in Table 2 below.
[0221]
[0222] As shown in Table 2 above, it was confirmed that when the sulfur (S) content in the negative electrode was controlled to be 3 wt % or less at SOC 100, the lithium-sulfur battery having long life characteristics could be realized.
Claims
1. A lithium-sulfur battery comprising a positive electrode comprising a sulfur-carbon composite, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, wherein the negative electrode comprises a lithium metal layer and a solid electrolyte interface (SEI) layer on at least one surface of the lithium metal layer, and The weight of sulfur (S) present in the negative electrode at a state of charge (SOC) of 100 is 3 wt % or less based on the total weight of the negative electrode.
2. The lithium-sulfur battery according to claim 1, wherein at SOC 100, the lithium-sulfur battery has a potential of 2.4 V to 2.7 V.
3. The lithium-sulfur battery according to claim 1, wherein the weight of the sulfur (S) in the negative electrode is 3 wt% or less based on the sum of the weights of the sulfur (S) and lithium (Li) in the negative electrode.
4. The lithium-sulfur battery according to claim 3, wherein the weight of the sulfur (S) in the negative electrode is 2 wt% or less based on the sum of the weights of the sulfur (S) and the lithium (Li) in the negative electrode. 5 . The lithium-sulfur battery according to claim 3 , wherein the weight of the sulfur (S) in the negative electrode is 1 wt % or less based on the sum of the weights of the sulfur (S) and the lithium (Li) in the negative electrode. 6 . The lithium-sulfur battery according to claim 1 , wherein the negative electrode has a thickness of 120 μm or less. 7 . The lithium-sulfur battery according to claim 1 , wherein the negative electrode has a thickness of 70 μm or less. 8 . The lithium-sulfur battery according to claim 1 , wherein a sulfur / carbon weight ratio (S / C weight ratio) of the sulfur-carbon composite is 2.5 g / g or less.
9. The lithium-sulfur battery according to claim 1, wherein the positive electrode comprises a current collector and a positive electrode active material layer comprising the sulfur-carbon composite, and The weight of the sulfur-carbon composite is greater than or equal to 90 wt % based on the total weight of the positive electrode active material layer. 10 . The lithium-sulfur battery according to claim 1 , wherein a weight ratio of the electrolyte to sulfur in the sulfur-carbon composite (E1 / S weight ratio) is 3.5 g / g or less.
11. The lithium-sulfur battery according to claim 1, wherein the electrolyte comprises a non-aqueous solvent, a lithium salt and an additive.
12. The lithium-sulfur battery of claim 11, wherein the additive comprises a nitrogen compound.
13. The lithium-sulfur battery of claim 11, wherein the additive comprises lithium nitrate (LiNO3). 14 . The lithium-sulfur battery according to claim 11 , wherein the additive is contained in an amount of 1 wt % to 5 wt % based on the total weight of the electrolyte. 15 . The lithium-sulfur battery according to claim 11 , wherein a ratio of the molar concentration of the lithium salt to the molar concentration of the additive (molar concentration of the lithium salt / molar concentration of the additive) is 0.5 to 5.
16. The lithium-sulfur battery according to claim 1, wherein the lithium-sulfur battery has a life of more than 190 cycles when charge and discharge cycles are repeated at a rate of 0.3 to 0.5 C in the range of 1.8 V to 2.5 V at room temperature.
17. The lithium-sulfur battery according to claim 16, wherein the room temperature is a temperature of 23°C to 25°C.
18. The lithium-sulfur battery according to claim 1, wherein the lithium-sulfur battery has an energy density of 300 Wh / kg or more.
19. A method for evaluating the life of a lithium-sulfur battery, the lithium-sulfur battery comprising a positive electrode comprising a sulfur-carbon composite, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, wherein the negative electrode comprises a lithium metal layer and a solid electrolyte interface (SEI) layer on at least one surface of the lithium metal layer, the evaluation method comprising: When the weight of sulfur (S) present in the negative electrode at a state of charge (SOC) of 100 is 3 wt % or less based on the total weight of the negative electrode, the lithium-sulfur battery is determined to have a long lifespan.
20. The evaluation method according to claim 19, wherein the long-life lithium-sulfur battery has a life of more than 190 cycles when charge and discharge cycles are repeated at a rate of 0.3 to 0.5 C in the range of 1.8 V to 2.5 V at room temperature.
Citation Information
Patent Citations
Etching method and etching device
KR1020230058000A
Manufacturing method of hollow high entropy metal oxide for lithium sulfur battery
KR1020230133560A